The Effect of Seaweed Combination on the Extract of Robusta Coffee (Coffea robusta) Waste Extract in Producing Facial Mask Products - Muhammad Ridwan Harahap; Nizar Mauliza; Anjar Purba Asmara; Elsa Citra Lestari; Winda Afriani (Fakultas Ilmu Kesehatan Universitas Setia Budi Surakarta, 2020)
Aceh is one of the biggest coffee producers in Indonesia’s province. The coffee farmers separate the coffee beans with the flesh of the fruit for processing the seeds, while the coffee fruit is considered as waste used as animal feed. Based on existing research, the coffee flesh produced contains polyphenol compounds as antibacterial. A very promising sea product from Aceh is seaweed. Brown seaweed (Sargassum sp.) is very common in the west coast of Aceh province. One of the derivatives is alginate. In this study, a combination of polyphenols extracts from coffee flesh and alginates from seaweed Sargassum sp. used as a basic ingredient in making face masks. Tests on organoleptic observations, pH testing, testing time of dried preparations, and testing of bacterial activity have been carried out in this study. In addition, variations in the mixture preparation based on the particle size of alginate powder have also been carried out in this study. The results obtained indicate that the yield produced from coffee fruit extracts is 5.86%, the highest yield of alginate is by potassium carbonate of 40.77%, the acidity of the combination is 4.5 - 6.5. For preparations, drying time has an average estimated time of approximately 6 minutes. Bacterial activity test showed that K2CO3 extracting agent concentration of 2% was strong against bacterial growth with a clean area of ​​14 mm. With these results, it can be seen the combination is able to inhibit the rate of bacterial growth, so it is recommended for alternative ingredients in the manufacture of cosmetics pharmaceutical industry masks.